Reduction of Negative Charge in Mercaptoacetyl-Based Chelators Influences the Biodistribution of Prostate-Specific Membrane Antigen-Targeting Pseudopeptides Labeled with Technetium-99m; ACS Pharmacology & Translational Science; Vol. 8, iss. 10 - Bezverkhniaia E. A. Ekaterina Aleksandrovna; Kanellopoulos P. Panagiotis; Rosenstrom U. Ulrik; Tolmachev V. M. Vladimir Maksimilianovich; Orlova A. M. Anna Markovna (2025, 2025)
Title screen